From material discrete memory patterns to the study of demagnetisation-like processes - Tourabi, A.; Guelin, P.; Favier, D.; Nowacki, W.K. (Archives of Mechanics, 1997)
The present paper is an attempt to study the links between the constitutive pattern of the idealized behaviour of pure hysteresis and the general theory of demagnetisation-like processes of real materials. Modelling based on this discrete-memory pattern has been previously introduced, and used to describe rather successfully the puzzling properties of various deformable materials ranging from granular media to shape memory alloys and deformable ferromagnets or ferroelectrics. However, one of the five basic ingredients of the pattern has not been, up to now, studied extensively: it has been introduced rather as an assumption, namely that of the general possibility to obtain recurrent recovery of a unique thermomechanical initial neutral state. Therefore the aim of this paper is threefold: firstly, to give some tensorial mechanical examples suggesting that the fifth ingredient of the pattern is relevant with respect to the others; secondly, to suggest the importance of a general study of demagnetisation-like processes, purely mechanical or not; thirdly, to suggest that the fifth ingredient is not only relevant on the theoretical grounds and of importance at the level of physical principles, but may be also justified owing to data from now on available.